Mídia, cotidiano e identidade: o caso do canal 4, de Currais Novos (RN) - Silva, Maríllia Graziella Oliveira da (2017)
This dissertation has as its main objective, to investigate in which way the mediatization of everyday life in Currais Novos (RN) by local channel 4 contributes to the construction of local identity. The channel belongs to the first cable TV network in the North/Northeast regions of Brazil, Sidy´s TV a Cabo, created in 1992 by entrepreneur Siderley Menezes. Based on empiricism, we realized that the relationship responsible for identity construction and appropriation is of a mutuality nature: channel 4 appropriates itself of Currais Novos´s identity to transmit its content to the point that its content also contributes construct local identity. The method of choice was case study (YIN, 2005), starting with a bibliographic inquiry approaching specifically the concepts of mediatization, everyday life, local media and identity. In order to optimize the empirically collected evidences, the methodology was supported by data triangulation, obtained through three distinct techniques: in-depth interviews (DUARTE, 2012), participant observation (PERUZZO, 2012) and documentation. A brief timeline, explaining the arrival of cable TV in Brazil is presented, as well as the historic and economic traits of Currais Novos (RN), and the details of Sidy´s TV a Cabo´s implementation and consolidation in the city. Finally, this paper points to the necessity of more in-depth media researches in the region, specially contemplating all the local content television channels and in which way they reconfigure the social dynamics of small town residents.